Development of Teaching Module Based on the Merdeka Curriculum with the Application of Character Integrated Problem Solving Model - Nurhafidhah, Nurhafidhah; Mauliza*, Mauliza; Yani, Ahmad Fauzi Syahputra; Aprilia, Rapita; Zatya, Ismi; Wan Mustapha, Wan Zumusni (Universitas Syiah Kuala, 2024)
Starting in 2022, the merdeka curriculum can be implemented by educational units even though they are not Driving Schools. One of the learning tools needed to implement the independent curriculum is teaching modules. The lack of sources of information and examples of the application of the character integrated learning model in developing teaching modules is an urgency in this research. The aim of this research is to develop an independent curriculum teaching module by implementing an integrated problem solving model of character education in science lessons that is valid and feasible and can be well received by teachers as product users. This research uses research and development (RD) methods, with the ADDIE (analysis, design, development, implement and evaluation) development model. The instruments used were interview guides, questionnaire sheets and observations. The population in this research is teachers at Langsa City State Middle School, the research sample was taken using a purposive sampling technique. The product produced in this research is a science learning teaching module with an integrated problem solving model of character education. The teaching module developed is valid and suitable for use in science learning, with a percentage score of 89.2% in the very valid category. Apart from that, the teacher response to the teaching module product was 89% in the very good category. Therefore, it is recommended that this integrated problem solving model of character education science teaching module be implemented in learning to determine its effectiveness and influence on student learning outcomes.